2008
DOI: 10.1055/s-2008-1068112
|View full text |Cite
|
Sign up to set email alerts
|

Die Leistenhernie im Alter

Abstract: By retrospective analysis of the medical records from 1978-1985, the rates of incarceration, postoperative complications and lethality were determined with particular consideration of elective and emergency operations. The proportion of over 60 year old patients with inguinal hernia was 37.3%. The rate of incarceration in these patients (9.8%) was more than five times as high as in patients under 60 years old (1.8%); with increasing age, it rose from 3% to 36%. The Bassini technique predominated in the surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[7] It has been reported that postoperative complications were significantly more common after emergency treatment of incarcerated inguinal hernias then after elective repair of hernias in elderly. [1011] One of the earliest successful repairs of incarcerated inguinal hernia with laparoscopy was reported by Watson in 1993. [8]…”
Section: Discussionmentioning
confidence: 99%
“…[7] It has been reported that postoperative complications were significantly more common after emergency treatment of incarcerated inguinal hernias then after elective repair of hernias in elderly. [1011] One of the earliest successful repairs of incarcerated inguinal hernia with laparoscopy was reported by Watson in 1993. [8]…”
Section: Discussionmentioning
confidence: 99%